Analisis Dampak Pembangunan Bandara Internasional Yogyakarta Ditinjau dari Perekonomian Masyarakat Kecamatan Temon Kabupaten Kulon Progo - Lilis Lilis Setiyaningrum; Eny Sri Haryati (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
Yogyakarta International Airport is an international airport built in Temon District, Kulon Progo Regency, Yogyakarta Special Region. There are five villages affected by the construction of Yogyakarta International Airport, namely Glagah, Sindutan, Palihan, Kebonrejo, and Jangkaran. This research aims to find out the economic impact on the community due to the construction of Yogyakarta International Airport and the efforts of the community in dealing with the impact caused. This research uses qualitative methods. The data for this study was obtained from interviews conducted with several villagers affected by the construction of Yogyakarta International Airport, the Deputy Head of Trade and Industry Office Kulon Progo, the Palihan Village Head, and the Head of Jangkaran Village. This research was conducted in the Temon District in October 2021. From the results of the study, it was concluded that the Yogyakarta international airport has an impact on the economy of the surrounding community, with some differences of opinion about the economic changes felt by affected residents. Some of the factors that cause differences in economic change in society are employment and the utilization of business opportunities. Keywords : Impact of Airport Development, Community Economy, Yogyakarta International Airport